Negative electrode material and battery

By designing a negative electrode material with a cladding layer in a lithium-ion battery, controlling the pore volume and particle space collapse ratio, the powderization problem caused by volume expansion of the silicon negative electrode material is solved, and the circulation performance and structural stability of the battery are improved. Higher electrochemical properties and lower expansion rates are achieved.

CN119275277APending Publication Date: 2025-01-07BTR NEW MATERIAL GRP CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411693736.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Silicon negative electrode materials are powdered due to volume expansion in lithium-ion batteries, destroying the contact between active substances and electrolytes, reducing electrochemical properties and cycling stability, making it difficult to commercially apply.

Method used

Design a negative electrode material, including active substances and cladding, control the pore volume and particle space collapse ratio, adjust the rigid strength of the material, improve structural stability and reduce expansion rate, and use pulsed chemical vapor deposition technology to be used in the negative electrode material. A second material is deposited inside the precursor to form a conductive network and a pore structure.

Benefits of technology

It improves the circulation and electrochemical properties of the negative electrode material, reduces the expansion rate, enhances structural stability and conductivity, solves the problems of crushing and cracking of the material during the pressing roller process, and improves the first effect and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275277A_ABST
    Figure CN119275277A_ABST
Patent Text Reader

Abstract

The negative electrode material comprises an active substance and a coating layer, the coating layer is arranged on at least part of the surface of the active substance, the active substance comprises a first matrix and a second matrix, the negative electrode material is provided with pores, the pore volume of the negative electrode material is M, the pore volume measured after the negative electrode material is subjected to pressure maintaining for 1 h under the pressure of 80 Mpa is N, the particle space collapse ratio of the negative electrode material is P, P = (M-N) / M, M is larger than or equal to 0.002 cm < 3 > / g and smaller than or equal to 0.12 cm < 3 > / g, and P is larger than or equal to 0.05 and smaller than or equal to 0.85. The rigid strength of the negative electrode material is modulated by controlling the pore volume of the negative electrode material before and after pressurization, so that the electrochemical performance of the negative electrode material is improved while the structural stability of the negative electrode material is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is a divisional application with application number 202411131888.2, application date August 19, 2024, and invention name “Negative Electrode Materials and Batteries”. Technical Field

[0003] The present application relates to the technical field of battery materials, and in particular to a negative electrode material and a battery using the negative electrode material. Background Art

[0004] Lithium-ion batteries are widely used in electric vehicles and consumer electronics due to their high energy density, excellent output power, long cycle life, and low environmental pollution. To further improve the energy density of batteries, the research and development of silicon anode materials has become particularly important.

[0005] However, silicon anode materials undergo significant volume expansion during lithium insertion and extraction, causing them to pulverize and fall off the current collector during charge and discharge. This disrupts the electrical contact between the active material and the current collector, leading to reduced electrochemical performance, capacity decay, and cycling stability, making commercial application difficult. Summary of the Invention

[0006] In order to solve at least one of the above technical problems, an embodiment of the present application provides a negative electrode material.

[0007] In addition, an embodiment of the present application further provides a battery comprising the aforementioned negative electrode material.

[0008] The present application provides a negative electrode material, including an active material and a coating layer, wherein the coating layer is provided on at least a portion of the surface of the active material, the active material includes a first matrix and a second matrix, the negative electrode material has pores, the pore volume of the negative electrode material is M, the pore volume of the negative electrode material measured after being held at a pressure of 80 MPa for 1 hour is N, and the particle space collapse ratio of the negative electrode material is P, P = (MN) / M, wherein 0.002 cm 3 / g≤M≤0.12cm 3 / g, 0.05≤P≤0.85.

[0009] In some possible embodiments, the first matrix includes a single substance or a combination of at least one selected from silicon, germanium, antimony, tin, and boron.

[0010] In some possible embodiments, the first matrix includes a silicon-based material, and the silicon-based material includes at least one of amorphous silicon, crystalline silicon, a composite of crystalline silicon and amorphous silicon, silicon oxide, and a silicon alloy.

[0011] In some possible embodiments, the second matrix satisfies at least one of the following conditions:

[0012] (1) The second matrix includes a carbon material, wherein the carbon material includes at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, and graphene;

[0013] (2) The second matrix includes a non-carbon material, and the non-carbon material includes at least one of a metal, a metal oxide, a silicide, a silicate, a phosphate, a titanate, and an aluminum borate.

[0014] In some possible embodiments, at least some of the particles of the second matrix are located inside the particles of the first matrix, and / or at least some of the particles of the first matrix are located inside the particles of the second matrix.

[0015] In some possible embodiments, the coating layer satisfies at least one of the following conditions:

[0016] (1) The coating layer includes a carbon material, wherein the carbon material includes at least one of graphene, soft carbon, and hard carbon;

[0017] (2) The coating layer includes a metal oxide layer, and the material of the metal oxide layer includes at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide and vanadium oxide;

[0018] (3) The coating layer includes a nitride layer, and the material of the nitride layer includes at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride;

[0019] (4) The thickness of the coating layer is 0.1 nm to 100 nm.

[0020] In some possible embodiments, the silicon-based material satisfies at least one of the following conditions:

[0021] (1) The average particle size of the primary particles of the silicon-based material is 1 nm to 100 nm;

[0022] (2) The average grain size of the silicon-based material is 0.5 nm to 15 nm.

[0023] In some possible embodiments, the negative electrode material satisfies at least one of the following conditions:

[0024] (1) The median particle size of the negative electrode material is 0.2 μm to 15 μm;

[0025] (2) The specific surface area of ​​the negative electrode material is 0.8 m 2 / g~15m 2 / g;

[0026] (3) The average diameter of the pores is 0.5 nm to 20 nm;

[0027] (4) The powder compaction density of the negative electrode material is 0.8 g / cm 3 ~1.5g / cm 3 .

[0028] In some possible embodiments, the negative electrode material satisfies at least one of the following conditions, calculated by mass percentage:

[0029] (1) The second matrix comprises a carbon material, and the carbon content of the negative electrode material is 5% to 70% based on the mass of the negative electrode material;

[0030] (2) Based on the mass of the negative electrode material, the content of oxygen in the negative electrode material is less than or equal to 10%.

[0031] An embodiment of the present application further provides a battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet includes the negative electrode material as described above.

[0032] Compared to the prior art, the negative electrode material provided in the embodiments of the present application modulates the rigidity and strength of the negative electrode material by controlling the pore volumes M and N before and after pressurization. Based on the pore volume M of the negative electrode material before pressurization and the pore volume N of the negative electrode material after pressurization, the particle space collapse ratio P of the negative electrode material is controlled within an appropriate range. By adjusting the rigidity and strength of the negative electrode material, on the one hand, the pulverization problem caused by excessive stress generated during the lithium insertion and deintercalation process of the negative electrode material is improved, the structural stability of the negative electrode material during the lithiation process is enhanced, and the cycle performance of the negative electrode material is improved. On the other hand, the internal collapsibility of the negative electrode material is utilized to cause the negative electrode material to expand inward, thereby reducing the degree of deformation of the entire negative electrode material particle surface, reducing the expansion rate of the negative electrode material, and thereby improving the initial coulombic efficiency of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a process flow chart of the method for preparing the negative electrode material provided in the embodiment of the present application.

[0034] Figure 2 A schematic diagram of the structure of the battery provided in an embodiment of the present application.

[0035] Figure 3 This is a scanning electron microscope image of the negative electrode material of Example 1 of the present application.

[0036] Figure 4 This is the X-ray diffraction pattern of the negative electrode material of Example 1 of the present application.

[0037] Figure 5 This is a cycle performance curve of a battery prepared with the negative electrode material of Example 1 of the present application. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the embodiments described are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making any creative work shall fall within the scope of protection of the present application.

[0039] To address the poor conductivity and cycle stability of negative electrode materials, researchers have attempted to use coating methods. However, existing coating preparation processes are quite complex, and simple coating layers can cause significant volume expansion and contraction of the negative electrode material during charge and discharge, potentially leading to rupture and failure of the coating layer. This inability to protect the negative electrode material from structural damage and effectively improve its electrochemical performance is ineffective.

[0040] The inventors of the present application have found that changes in the number and volume of pores in the negative electrode material before and after being compressed have a significant impact on the volume expansion and performance of the negative electrode material. To this end, the present application provides an embodiment of a negative electrode material, which includes an active material, the active material including a first matrix and a second matrix, the negative electrode material has pores, the pore volume of the negative electrode material is M (i.e., the pore volume of the negative electrode material in a natural state or an unpressurized state), the pore volume of the negative electrode material measured after being pressurized at 80 MPa for 1 hour is N, and the particle space collapse ratio P of the negative electrode material is specified as (MN) / M, i.e., P=(MN) / M, wherein 0.002 cm 3 / g≤M≤0.12cm 3 / g, 0.05≤P≤0.85. By controlling the pore volumes M and N of the negative electrode material before and after pressurization, and thereby adjusting the particle space collapse ratio P of the negative electrode material within an appropriate range, the rigidity and strength of the negative electrode material are adjusted, thereby improving the various electrochemical properties of the negative electrode material while ensuring the structural stability of the negative electrode material, such as improving the cycle stability of the battery prepared with the negative electrode material; solving the problem of the electrode sheet prepared with the negative electrode material being prone to breakage and cracking during the roller pressing process, and improving the poor processing performance of the negative electrode material.

[0041] Specifically, under appropriate pressure, controlling the spatial collapse ratio P of the negative electrode material particles within the range of 0.05 to 0.85 can improve the rigidity of the material, moderately reduce the pores inside the negative electrode material, reduce the deformation of the outer surface of the negative electrode material, ensure the formation of a stable solid electrolyte film on the surface of the negative electrode material, and thus improve the first coulombic efficiency of the negative electrode material. If the spatial collapse ratio of the negative electrode material particles is too low (lower than 0.05), the huge stress generated after the lithiation of the first matrix (such as silicon) will cause the entire negative electrode material to break, resulting in deterioration of the cycle performance of the battery prepared with the negative electrode material; if the spatial collapse ratio of the negative electrode material particles is too high (higher than 0.85), the rigidity of the negative electrode material is weak and there are more internal pores. Although it can effectively alleviate the volume expansion of the first matrix, due to the large volume shrinkage of the negative electrode material, the electrolyte will be absorbed into the material, causing side reactions between the negative electrode material and the electrolyte, thereby causing serious capacity decay of the battery prepared with the negative electrode material.

[0042] The size of the pore volume M of the negative electrode material directly affects the spatial collapse ratio P of the negative electrode material particles. In order to control the particle spatial collapse ratio P within the range of 0.05 to 0.85, the negative electrode material needs to have a suitable pore volume M.

[0043] The pore volume M of the negative electrode material needs to be controlled within 0.002 cm 3 / g~0.12cm 3 / g range, this is because the pore volume M is too large (greater than 0.12cm 3 / g) will result in the negative electrode material structure being too loose and the pore volume M being too small (less than 0.002cm 3 / g) will cause the negative electrode material particles to be unable to effectively alleviate the volume expansion of active materials such as silicon particles, and will be broken and pulverized. During the cycle of the battery prepared by the negative electrode material, the loose structure of the negative electrode material or the pulverization of the particles will cause a significant change in volume, resulting in capacity decay. The pore volume M is controlled at 0.002cm 3 / g~0.12cm 3 / g, which can effectively extend the service life and cycle stability of batteries prepared with negative electrode materials. Limiting the range of pore volume M can also adjust the specific surface area and ion diffusion path of the negative electrode material, which is beneficial to improving the electron transfer rate and ion diffusion rate of the negative electrode material, thereby improving the charge and discharge efficiency of batteries prepared with negative electrode materials.

[0044] The pore volume M of the negative electrode material originates from the pores within the negative electrode material. By adjusting the pore size within the negative electrode material, the pore volume of the negative electrode material is adjusted, and the spatial collapse ratio of the negative electrode material particles is controlled to meet the stability and performance requirements of the battery material during use.

[0045] In some embodiments, the average diameter of the pores of the negative electrode material can be 0.5nm to 20nm, and can be 0.5nm, 1nm, 2nm, 5nm, 8nm, 10nm, 15nm or 20nm, etc., and of course it can also be other values ​​within the above range, which is not limited here. The diameter of the pores affects the specific surface area of ​​the negative electrode material. Smaller pores usually have a higher specific surface area, which is conducive to the diffusion of electrolytes and ions, while larger pores can improve the expansion performance of the negative electrode material, which helps the stability and cycle life of the negative electrode material. Within the above range, the negative electrode material can reduce the penetration of electrolytes into the interior of the negative electrode material while maintaining structural stability and promoting the rapid diffusion of ions, thereby reducing the side reactions between the negative electrode material and the electrolyte. At the same time, the pore volume and particle space collapse ratio of the negative electrode material are further adjusted, and the average diameter of the pores can be 2nm to 15nm.

[0046] In some embodiments, the first matrix may include a single substance or a combination of at least one selected from silicon, germanium, antimony, tin, and boron. For example, silicon particles used as a component of the negative electrode active material can increase the specific capacity of the negative electrode material, thereby increasing the energy density of the battery prepared with the negative electrode material.

[0047] In some embodiments, the first matrix may include a silicon-based material, which may include amorphous silicon, crystalline silicon, or a composite of crystalline silicon and amorphous silicon. For example, the first matrix includes amorphous silicon, which expands isotropically during lithium insertion, thereby reducing the collapse of pores in the negative electrode material, inhibiting the rapid attenuation of the specific capacity of the negative electrode material, and further improving the lithium insertion cycle performance of the negative electrode material.

[0048] In some embodiments, the first matrix may include a silicon-based material, and the silicon-based material may include at least one of silicon oxide and silicon alloy.

[0049] In some embodiments, the morphology of the first matrix may include at least one of a dot shape, a sphere shape, an ellipsoid shape, and a plate shape.

[0050] In some embodiments, the purity of the first matrix can be greater than 99%. Taking silicon particles as an active material as an example, high-purity silicon particles are more conducive to Li-Si alloying with lithium, thereby improving the cycle performance of lithium-ion batteries.

[0051] In some embodiments, the second matrix may include a carbon material, which may include at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesocarbon microbeads, carbon nanotubes, carbon nanofibers, and graphene. The second matrix may be any of the above materials, all of which can form a conductive network with the first matrix.

[0052] In some embodiments, the second matrix may include a non-carbon material, and the non-carbon material may include at least one of a metal, a metal oxide, a silicide, a silicate, a phosphate, a titanate, and an aluminum borate. It is understandable that the non-carbon material adopts the above materials, all of which have good strength and rigidity, so that the negative electrode material can have a higher compaction density during the battery preparation process, which can improve the structural stability of the negative electrode material, reduce the particle breakage and pulverization of the negative electrode material, and help improve the cycle performance of the negative electrode material. At the same time, due to its electronic insulation properties, the non-carbon material usually has good ionic conductivity and can play a role similar to that of an artificial SEI film, which can slow down the subsequent formation of a natural SEI film, reduce the direct contact between the negative electrode material and the electrolyte, and reduce the occurrence of side reactions.

[0053] In some embodiments, the metal oxide may include at least one of aluminum oxide, zirconium oxide, germanium dioxide, and manganese dioxide.

[0054] In some embodiments, the silicide may include at least one of silicon carbide and silicon nitride.

[0055] In some embodiments, the silicate may include at least one of cordierite, mullite, and zeolite. It is understood that the silicate of the present application is mainly a natural silicate mineral, wherein cordierite (magnesium aluminum silicate) has a chemical formula of Mg2Al4Si5O 18 , which may contain elements such as Na, K, Ca, Fe and Mn and H2O; mullite, whose chemical formula is 3Al2O3-2SiO2; zeolite (aluminosilicate), whose chemical formula is A m B p O 2p nH2O, where A represents a cation, usually a monovalent or divalent metal ion such as Ca, Na, K, Ba, or Sr; B represents the basic unit that constitutes the zeolite framework, namely Si and Al atoms; p represents the valence of the cation; m represents the number of cations A; and n represents the number of water molecules.

[0056] In some embodiments, the phosphate may include at least one of aluminum phosphate, magnesium phosphate, calcium phosphate, titanium phosphate, chromium phosphate, cobalt phosphate, nickel phosphate, germanium phosphate, zirconium phosphate, niobium phosphate, molybdenum phosphate, tantalum phosphate, tungsten phosphate, and lanthanum phosphate.

[0057] In some embodiments, the titanate may include at least one of calcium titanate, iron titanate, lithium titanate, and barium titanate.

[0058] In some embodiments, in the negative electrode material, at least a portion of the particles of the second matrix are located within the particles of the first matrix. For example, a silicon-based material is selected as the first matrix and a carbon material is selected as the second matrix. The silicon material exists in the form of silicon crystals, and multiple silicon material particles constitute the matrix of the negative electrode material. With the silicon material as the matrix, the negative electrode material can adjust various properties of the negative electrode material by utilizing the nanostructure and pore distribution of the silicon material. At least a portion of the carbon material can be located within the pores of the silicon material, and together with the silicon material, form the pores of the negative electrode material. In this way, the carbon material is filled into the pores of the silicon material, retaining a certain pore volume to obtain a suitable particle space collapse ratio, thereby adjusting the rigidity and strength of the negative electrode material. Of course, in other embodiments, in the negative electrode material, at least a portion of the particles of the first matrix are located within the particles of the second matrix. For example, a silicon-based material is selected as the first matrix and a carbon material is selected as the second matrix. The silicon material exists in the form of silicon particles, and the carbon material particles constitute the matrix of the negative electrode material. With the carbon material as the matrix, the negative electrode material can adjust various properties of the negative electrode material by utilizing the pore distribution of the carbon material. At least a portion of the silicon material can be located within the pores of the carbon material, and together with the carbon material, form the pores of the negative electrode material. This allows the silicon material to fill the pores of the carbon material, retaining a certain pore volume to achieve an appropriate particle space collapse ratio, thereby adjusting the rigidity and strength of the negative electrode material.

[0059] In some embodiments, the average particle size of the primary particles of the silicon-based material can be 1nm to 100nm, and can be 1nm, 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, etc., and of course it can also be other values ​​within the above range, which are not limited here. Controlling the average particle size of silicon particles in the silicon-based material between 1nm and 100nm can adjust the specific surface area and electron transport path of the negative electrode material, which is beneficial to improving the electrochemical performance of the negative electrode material. Further, the average particle size of the primary particles of the silicon-based material can be 5nm to 50nm. In the present invention, the expression "primary particle" refers to the primary structure of a single particle, and the expression "secondary particle" refers to an aggregate of primary particles aggregated by physical or chemical bonding between primary particles, that is, a secondary structure, without deliberately performing an aggregation or combination process of the primary particles that constitute the secondary particles.

[0060] In some embodiments, the average grain size of the silicon-based material can be 0.5 nm to 15 nm, and can be 0.5 nm, 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, 12 nm, or 15 nm, etc., and can also be other values ​​within the above range, which is not limited here. Smaller nano-scale silicon grain sizes generally have higher specific surface areas, which are beneficial to charge transfer and ion diffusion of the negative electrode material, and inhibit volume expansion, thereby improving the electrochemical performance, stability, and cycle life of the negative electrode material. Further, the average grain size of the silicon-based material can be 2 nm to 10 nm.

[0061] Furthermore, the negative electrode material may further include a coating layer, which is disposed on at least a portion of the surface of the active material. The coating layer is beneficial for improving the structural stability and conductivity of the negative electrode material. The synergistic effect of the appropriate particle space collapse ratio of the negative electrode material and the uniform coating layer on the surface of the negative electrode material can further improve the structural stability of the negative electrode material during the lithiation process, reduce the expansion rate of the negative electrode material, facilitate the formation of a stable solid electrolyte film on the surface of the negative electrode material, and also facilitate the improvement of the conductivity of the negative electrode material, thereby improving the electrochemical performance of the negative electrode material.

[0062] In some embodiments, the coating layer may include a carbon material, which may include at least one of graphene, soft carbon, and hard carbon. Properly designing the carbon material feedstock for the negative electrode material can effectively inhibit volume expansion of the negative electrode material, reduce structural damage during cycling, and enhance the mechanical strength and compressive resistance of the negative electrode material.

[0063] In some embodiments, the coating layer may include a metal oxide layer, and the material of the metal oxide layer may include at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.

[0064] In some embodiments, the coating layer may include a nitride layer, and the material of the nitride layer may include at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride, and carbon nitride.

[0065] In some embodiments, the thickness of the coating layer can be 0.1nm to 100nm. For example, the thickness of the coating layer can be 0.1nm, 5nm, 10nm, 30nm, 50nm, 80nm, 100nm or any value within the range formed by any two of the above values. The coating layer can reduce the solubility of the negative electrode material, thereby reducing the amount of gas produced by the reaction of the dissolved active substance with the electrolyte. Controlling the thickness of the coating layer within the above range is beneficial to maintaining the stability of the particle structure of the negative electrode material during the cycle, and can reduce the exposed active substance on the surface of the negative electrode material. Further, the thickness of the coating layer can be 1nm to 50nm, and further, the thickness of the coating layer can be 1nm to 20nm, which is beneficial to the rapid and reversible deintercalation of lithium ions.

[0066] In some embodiments, the coating layer can be a single layer formed of a single material, a coating layer formed of a combination of multiple materials, a multi-layer coating layer formed of a single material, or a multi-layer coating layer formed of multiple materials. The layer structure of the coating layer can be selected according to actual needs. It is understood that a multi-layer coating structure has a higher density.

[0067] In some embodiments, the median particle size of the negative electrode material can be 0.2μm to 15μm, and can be 0.2μm, 0.5μm, 1μm, 2μm, 5μm, 10μm or 15μm, etc., and of course it can also be other values ​​within the above range, which is not limited here. The median particle size of the negative electrode material directly affects the specific surface area and electron transfer path of the negative electrode material. A smaller particle size usually means a larger specific surface area, which is conducive to the electrochemical reaction and the rapid charge transfer, thereby improving the power density and energy density of the battery; a smaller particle size can reduce the volume change of the material during the lithium ion insertion / extraction cycle, which helps to reduce the stress and deformation of the structure, thereby extending the cycle life of the battery; the range of the median particle size can further affect the pore structure and pore volume of the negative electrode material, and affect the particle space collapse ratio of the negative electrode material. Further, the median particle size of the negative electrode material can be 1μm to 10μm.

[0068] In some embodiments, the specific surface area of ​​the negative electrode material can be 0.8 m 2 / g~15m 2 / g, which can be 0.8m 2 / g、1m 2 / g, 2m 2 / g、5m 2 / g、8m 2 / g、10m 2 / g or 15m 2 / g, etc., of course, it can also be other values ​​within the above range, which is not limited here. Within the above range, it is conducive to the rapid progress of electrochemical reaction and charge transfer, thereby improving the electrochemical performance of the negative electrode material. Further, the specific surface area of ​​the negative electrode material can be 2m 2 / g~10m 2 / g.

[0069] In some embodiments, the powder compaction density of the negative electrode material can be 0.8 g / cm 3 ~1.5g / cm 3 , which can be 0.8 g / cm 3 , 0.9g / cm 3 , 1g / cm 3 , 1.1g / cm 3, 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 or 1.5g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here. Within the above compaction density range, the negative electrode material has a suitable charge transfer rate and electrolyte contact area, and also has suitable good structural stability. Further, the powder compaction density of the negative electrode material can be 1g / cm 3 ~1.2g / cm 3 .

[0070] In some embodiments, the carbon content of the negative electrode material can be 5% to 70% by mass, based on the mass of the negative electrode material, and can be 5%, 10%, 20%, 30%, 40%, 50%, 60% or 70% by weight, etc., and can also be other values ​​within the above range, which are not limited here. Within the above range, by adjusting the carbon content, the electrochemical performance and structural stability of the negative electrode material can be optimized. Further, the carbon content of the negative electrode material can be 10% to 60%.

[0071] In some embodiments, the negative electrode material further contains oxygen. Calculated as a percentage by mass, based on the mass of the negative electrode material, the mass fraction of oxygen in the negative electrode material may be less than or equal to 10%, and may be, for example, 1%, 3%, 5%, 8%, or 10%, etc., and of course, may also be other values ​​within the above range, which are not limited here. The introduction of a certain amount of oxygen can affect the structure and chemical properties of the negative electrode material and adjust the pore structure of the negative electrode material. During the synthesis of the negative electrode material, oxygen within the above content range can form oxides or functional groups with a high oxygen content with carbon and silicon atoms. These functional groups can form pores in the negative electrode material or adjust the distribution and size of the pores in the negative electrode material; they can also improve the mechanical properties and structural stability of the negative electrode material; improve the electronic conductivity of the negative electrode material and the kinetic characteristics of the electrochemical reaction, which helps to improve the charge and discharge efficiency of the battery prepared with the negative electrode material; in addition, it may also affect the surface chemical properties of the negative electrode material, such as the formation of surface active sites, further promoting the interaction between the negative electrode material and the electrolyte, and optimizing the overall performance of the battery.

[0072] Compared with the prior art, the negative electrode material provided in the embodiments of the present application has the following beneficial effects:

[0073] 1. The embodiment of the present application controls the pore volume M and N of the negative electrode material before and after pressurization, controls the particle space collapse ratio P of the negative electrode material within the range of 0.05 to 0.85, and adjusts the rigidity strength of the negative electrode material. On the one hand, it improves the pulverization problem caused by excessive stress generated by the first matrix in the negative electrode material during the lithium insertion and extraction process, improves the structural stability of the negative electrode material during the lithiation process, and improves the cycle performance; on the other hand, it utilizes the internal collapsible ability of the negative electrode material to guide the negative electrode material to expand inward, so that the deformation of the entire particle surface is small, thereby improving the first efficiency of the battery prepared by the negative electrode material, and effectively reducing the expansion rate of the negative electrode material. Thereby, it ensures that the volume expansion effect of the negative electrode material is reduced, the external deformation of the negative electrode material is stabilized, and a stable solid electrolyte membrane is formed, thereby improving the electrochemical performance of the negative electrode material, such as improving the cycle stability of the battery prepared by the negative electrode material; solves the problems of the electrode sheet prepared by the negative electrode material being prone to breakage and cracking during the roller pressing process, and solves the problem of poor processing performance of the negative electrode material.

[0074] 2. The negative electrode material provided in the embodiments of the present application deposits a second matrix within the first matrix to form pores, thereby adjusting the pore volume of the negative electrode material, controlling the spatial collapse ratio of the particles of the negative electrode material, and thereby reducing the expansion rate of the negative electrode material and improving the electrochemical performance of the negative electrode material. In addition, the negative electrode material also has a coating layer. The formation of the coating layer on the surface of the negative electrode material can reduce the amount of negative electrode material dissolved during the cycle, thereby reducing the side reactions caused by the dissolved first matrix contacting the electrolyte.

[0075] See also Figure 1 As shown, the preparation method of the negative electrode material provided in the embodiment of the present application specifically includes the following steps:

[0076] Step S1, sintering the first material once to obtain a first product.

[0077] Specifically, the first material is placed in a reaction apparatus (e.g., an atmosphere furnace), sintered once under a protective atmosphere, and then cooled to obtain a first product. The primary sintering of the first material is primarily intended to pre-treat the first material, prevent oxidation, and promote thermal decomposition and crystallization of the first material. This stabilizes the structure of the first product, prepares for subsequent chemical reactions and compounding steps, and ensures that the first product possesses a certain crystal structure and chemical activity.

[0078] In some embodiments, the first material may include a single substance or a combination of at least one selected from silicon, germanium, antimony, tin, and boron. For example, using silicon as the first material can increase the specific capacity of the prepared negative electrode material, thereby increasing the energy density of the battery prepared with the negative electrode material.

[0079] In some embodiments, the first material may include a silicon-based material, and the silicon-based material may include amorphous silicon, crystalline silicon, or a composite of crystalline silicon and amorphous silicon.

[0080] In some embodiments, the first material may include a silicon-based material, and the silicon-based material may include at least one of silicon oxide and silicon alloy.

[0081] In some embodiments, the morphology of the first material may include at least one of a dot shape, a sphere shape, an ellipsoid shape, and a flake shape.

[0082] In some embodiments, the purity of the first material can be greater than 99%. Taking silicon as the first material as an example, high-purity silicon is more conducive to Li-Si alloying with lithium, thereby improving the cycle performance of lithium-ion batteries.

[0083] In some embodiments, the median particle size D50 of the first material can be 0.1 μm to 20 μm, and can be 0.1 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm or 20 μm, etc. Within the above-defined range, it helps to ensure the uniformity and consistency of the first material during heat treatment and chemical reaction. At the same time, a smaller particle size helps to improve the specific capacity of the battery, reduce the volume expansion of the negative electrode material, etc. Further, the median particle size D50 of the first material can be 2 μm to 15 μm. The particle size test method of the above-mentioned first material can be a volume-based cumulative particle size distribution measured by a Malvern laser particle size analyzer (Mastersizer 3000) using a laser diffraction method. D50 represents the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%.

[0084] In some embodiments, the primary sintering is performed at a heating rate of 1°C / min to 20°C / min to a primary sintering temperature of 250°C to 1150°C and held for 3h to 12h. The primary sintering temperature may further be 500°C to 1000°C, and may be illustratively 250°C, 350°C, 400°C, 500°C, 600°C, 700°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc., and may be other values ​​within the above range, which are not limited in this application. Appropriate heating rates, sintering temperatures, and holding times facilitate pre-treating the first material to form a certain crystal structure, providing a basis for subsequent reaction with a metal reducing agent.

[0085] In some embodiments, the protective atmosphere may include at least one of argon, nitrogen, and helium to reduce the reaction of the first material with oxygen at high temperature to form oxides, thereby maintaining the purity and activity of the first material.

[0086] Step S2: mixing the first product with a metal reducing agent and performing secondary sintering to obtain a second product.

[0087] Specifically, the first product and a metal reducing agent are mixed in a certain proportion and then placed in a reaction apparatus (e.g., a reactor). A protective gas is introduced to displace the air, followed by secondary sintering. The second product is then cooled to obtain the second product. The addition of the metal reducing agent is intended to chemically react with the first product. For example, if silicon is used as the first material, the first product reacts with the metal reducing agent to form a silicon-metal compound or a silicon-metal alloy. The secondary sintering process also helps ensure the uniformity and stability of the negative electrode material.

[0088] In some embodiments, the metal reducing agent may include at least one of magnesium powder, aluminum powder, and lithium powder. These metal reducing agents all have good reducing properties, facilitating the reduction and alloying of the first product. Furthermore, the introduction of the metal reducing agent also helps improve the conductivity, ion diffusion performance, and cycle stability of the negative electrode material.

[0089] In some embodiments, the mass ratio of the first product to the metal reducing agent is 1:(0.2-1.2), and can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, or 1:1.2, and can further be 1:(0.2-0.8). A suitable ratio can achieve a better reaction between the first product and the metal reducing agent.

[0090] In some embodiments, the secondary sintering is carried out by heating the temperature at a rate of 1°C / min to 30°C / min to a primary sintering temperature of 250°C to 950°C and holding the temperature for 1h to 48h, illustratively, 250°C, 350°C, 400°C, 500°C, 600°C, 700°C, 800°C, 850°C, 900°C or 950°C, etc., wherein the secondary sintering temperature may further be 300°C to 600°C, and of course other values ​​within the above range may also be used, which is not limited in this application. By appropriate heating rate, sintering temperature and holding time, it is possible to ensure that the reaction reaches a sufficient temperature and time, promote the reaction of the first product with the metal reducing agent, and improve the crystallinity and stability of the crystal structure of the second product.

[0091] Step S3: etching the second product to obtain a negative electrode material precursor.

[0092] Specifically, the second product obtained in step S2 is added to an etching solution in a certain proportion, purified under certain conditions, and then washed and dried to obtain a negative electrode material precursor. Acid etching can remove metal, byproducts, and other impurities on the surface of the second product to form the negative electrode precursor, improving the purity and activity of the negative electrode material precursor and reducing the impact of impurities on the electrochemical performance of the material. The clean negative electrode material precursor provides a good foundation for the pore formation step and the subsequent deposition of the second material.

[0093] In some embodiments, the etching solution may include one of hydrochloric acid, nitric acid, sulfuric acid, and hydrofluoric acid. These acidic solutions can effectively remove impurities such as metals and byproducts on the surface of the second product, thereby reducing the impact of impurities on the electrochemical properties of the subsequently prepared negative electrode material.

[0094] In some embodiments, the mass ratio of the second product to the etching solution can be 1:(5-20), and illustratively can be 1:5, 1:8, 1:10, 1:15, or 1:20, etc., and of course other values ​​within the above range can also be used, and this application is not limited thereto. By controlling the ratio of the second product to the etching solution, the surface of the second product is ensured to be fully exposed during the etching process, and the etching effect is optimized.

[0095] In some embodiments, the molar concentration of the etching solution can be 1 mol / L to 10 mol / L. The molar concentration of the etching solution affects the concentration of active ions or molecules in the etching solution, which directly affects the etching rate and effect. Selecting an appropriate molar concentration can achieve a desired etching effect in a shorter time while avoiding over-etching or incomplete etching.

[0096] In some embodiments, the etching reaction time may be 0.5 h to 10 h to ensure that the etching process is fully carried out so that impurities and unnecessary surface substances are completely removed.

[0097] In some embodiments, the temperature of the etching reaction is less than or equal to 35° C. Controlling a lower etching reaction temperature helps avoid an excessively fast chemical reaction rate and maintains the controllability and safety of the etching process.

[0098] In some embodiments, the mass content of oxygen in the negative electrode material precursor is less than 5%. Controlling the oxygen content can reduce the negative impact of impurities on the electrochemical properties of the material and ensure the electrochemical activity and stability of the negative electrode material precursor.

[0099] In some embodiments, the mass content of water in the negative electrode material precursor may be less than 1.2%. Low water content helps reduce the oxidation reaction of the negative electrode material precursor and maintain the purity and stability of the negative electrode material precursor.

[0100] In some embodiments, the median particle size of the negative electrode material precursor may be 0.1 μm to 15 μm, and may be 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm, or 15 μm, and may further be 1 μm to 10 μm. Of course, other values ​​within the above range are also possible and are not limited here. The median particle size affects the uniformity and surface area of ​​the negative electrode material precursor. An appropriate particle size range helps optimize the electrochemical reaction rate and energy storage capacity of the negative electrode material.

[0101] In some embodiments, the silicon grain size of the negative electrode material precursor may be 0.2 nm to 15 nm, and may be 0.2 nm, 0.5 nm, 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, 12 nm, or 15 nm, for example, and may further be 2 nm to 15 nm. Of course, other values ​​within the above range are also possible and are not limited here. Within the above range, the electrochemical reaction is facilitated and the charge transfer is rapid, thereby improving the electrochemical performance of the negative electrode material.

[0102] In some embodiments, the porosity of the negative electrode material precursor can be 25% to 55%, and can be exemplified by values ​​of 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, or 1:1.2, and can further be 35% to 55%. Other values ​​within the aforementioned range are also possible and are not limited herein. A moderate porosity helps increase the specific surface area of ​​the negative electrode material and the permeability of the electrolyte, promoting electrochemical reactions and material stability; and provides a foundation for the subsequent deposition of the second material and the formation of pores.

[0103] In some embodiments, the specific surface area of ​​the negative electrode material precursor can be 250 m 2 / g~550m 2 / g, which can be 250m 2 / g、300m 2 / g、350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g or 550m 2 / g, etc., and can be further 200m 2 / g~500m 2 / g, of course, it can also be other values ​​within the above range, which is not limited here. Within the above range, the negative electrode material precursor has a higher specific surface area, which is conducive to the subsequent contact reaction with the second material.

[0104] In some embodiments, the pore volume of the negative electrode material precursor may be 0.28 cm 3 / g~0.56cm 3 / g, which can be 0.28cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g or 0.56cm 3 / g, etc., and can be further 0.3cm 3 / g~0.5cm3 / g, and of course other values ​​within the above range are also possible and are not limited here. The higher pore volume in the negative electrode material precursor provides space for the subsequent deposition of the second material and ensures sufficient space to form the necessary pores to optimize the performance and stability of the negative electrode material.

[0105] Step S4: depositing a second material inside the particles of the negative electrode material precursor by pulsed chemical vapor deposition to obtain the negative electrode material.

[0106] Specifically, a negative electrode material precursor with a porous structure is placed in a reaction device (such as a reactor), the air therein is replaced with a protective gas, and after being heated to a certain temperature, a gas-phase second material is introduced by pulsed air intake. By controlling the amount of gas entering in a short time, the internal second material deposition rate and efficiency are changed. Then, the second material is continuously introduced to continue to deposit the carbon source in the pores inside the particles of the negative electrode material precursor. After keeping warm for a certain period of time, the second material undergoes a thermal cracking reaction, so that the second material is deposited inside the negative electrode material precursor, and holes are reserved inside the negative electrode material precursor to obtain the negative electrode material.

[0107] This step deposits the second material within the negative electrode precursor using pulsed chemical vapor deposition and creates pores. This pulsed gas flow allows for precise control of the second material's deposition rate within the negative electrode precursor, increasing the deposition rate from the inside out. This allows for the deposition of the second material while creating a portion of pores within the negative electrode precursor, thereby modulating the negative electrode material's pore volume and controlling the particle space collapse ratio.

[0108] In some embodiments, the second material may include a carbon material, which may include at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesocarbon microbeads, carbon nanotubes, carbon nanofibers, and graphene. The second material selected from the above materials can all be deposited within the negative electrode material precursor to form a conductive network.

[0109] In some embodiments, the second material may include a non-carbon material, and the non-carbon material may include at least one of metals, metal oxides, silicides, silicates, phosphates, titanates, aluminum borates, and the like.

[0110] In some embodiments, the metal oxide may include at least one of aluminum oxide, zirconium oxide, germanium dioxide, and manganese dioxide.

[0111] In some embodiments, the silicide may include at least one of silicon carbide and silicon nitride.

[0112] In some embodiments, the silicate may include at least one of cordierite, mullite, and zeolite. It is understood that the silicate of the present application is mainly a natural silicate mineral, wherein cordierite (magnesium aluminum silicate) has a chemical formula of Mg2Al4Si5O 18 , which may contain elements such as Na, K, Ca, Fe and Mn and H2O; mullite, whose chemical formula is 3Al2O3-2SiO2; zeolite (aluminosilicate), whose chemical formula is A m B p O 2p nH2O, where A represents a cation, usually a monovalent or divalent metal ion such as Ca, Na, K, Ba, or Sr; B represents the basic unit that constitutes the zeolite framework, namely Si and Al atoms; p represents the valence of the cation; m represents the number of cations A; and n represents the number of water molecules.

[0113] In some embodiments, the phosphate may include at least one of aluminum phosphate, magnesium phosphate, calcium phosphate, titanium phosphate, chromium phosphate, cobalt phosphate, nickel phosphate, germanium phosphate, zirconium phosphate, niobium phosphate, molybdenum phosphate, tantalum phosphate, tungsten phosphate, and lanthanum phosphate.

[0114] In some embodiments, the titanate may include at least one of calcium titanate, iron titanate, lithium titanate, barium titanate, and the like.

[0115] In some embodiments, the heating rate for vapor-phase carbon deposition can range from 1°C / min to 30°C / min. Controlling the heating rate can influence the transport and decomposition rate of the second material within the reaction apparatus. An appropriate heating rate can uniformly heat the anode material precursor within the reaction chamber to a reaction temperature suitable for thermal decomposition of the second material, while avoiding excessively rapid heating that could lead to non-uniform deposition or other adverse reaction effects.

[0116] In some embodiments, the reaction temperature of the vapor deposition may be 200° C. to 1050° C., and may be illustratively 200° C., 300° C., 350° C., 400° C., 500° C., 600° C., 700° C., 800° C., 850° C., 900° C., 950° C., 1000° C., or 1050° C., and may of course be other values ​​within the above range, which is not limited in this application, and may further be 500° C. to 1000° C. The reaction temperature is a key parameter affecting the thermal decomposition reaction rate and deposition quality of the second material. By carrying out the reaction within an appropriate temperature range, the thermal decomposition rate of the second material can be controlled, so that the second material is deposited inside the negative electrode material precursor and the desired pores are formed.

[0117] In some embodiments, the holding time of the vapor deposition can be 1 hour to 24 hours. Sufficient holding time is conducive to ensuring uniform deposition of the second material inside the negative electrode material precursor, forming a stable structure and pore distribution.

[0118] In some embodiments, the gaseous carbon source may include at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, pyrrole, and acetonitrile.

[0119] In some embodiments, the flow rate of the gaseous carbon source can be 0.1 L / min to 10 L / min, and can be 0.1 L / min, 0.5 L / min, 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min or 10 L / min, etc., and can of course be other values ​​within the above range, which is not limited in this application, and can further be 0.5 L / min to 5 L / min. Controlling the flow rate of the gaseous carbon source can adjust the rate and concentration of the carbon source entering the reaction device, thereby accurately controlling the carbon deposition rate of the carbon source inside the negative electrode material precursor.

[0120] In some embodiments, the pulse frequency can be 10 Hz to 500 Hz, and the pulse duration can be 10 ms to 800 ms. Pulsed air intake can control the short-term high-concentration input of the second material. By adjusting the pulse frequency and duration, the deposition process of the second material can be precisely controlled.

[0121] In some embodiments, the pulse duration is 1 hour to 8 hours. The pulse duration affects the deposition amount of the second material and the continuity of the reaction. An appropriate pulse duration can achieve sufficient deposition of the second material and form the required pores, thereby optimizing the electrochemical performance and cycle stability of the prepared negative electrode material.

[0122] Furthermore, a coating material can be deposited on the surface of the negative electrode material precursor by pulsed chemical vapor deposition to form a coating layer on the surface of the negative electrode material precursor, which is beneficial to reduce the amount of active substances dissolved in the negative electrode material during the cycle, thereby reducing the side reactions caused by the contact of dissolved silicon particles with the electrolyte; it is also beneficial to alleviate the volume expansion of the negative electrode material.

[0123] In some embodiments, the coating material may include a carbon material, which may include at least one of graphene, soft carbon, and hard carbon. Properly designing the carbon material feedstock for the negative electrode material can effectively inhibit the volume expansion of silicon particles, reduce structural damage to the negative electrode material during cycling, and enhance the mechanical strength and compressive resistance of the negative electrode material.

[0124] In some embodiments, the coating material may include a metal oxide layer, and the material of the metal oxide layer may include at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.

[0125] In some embodiments, the coating layer may include a nitride layer, and the material of the nitride layer may include at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride, and carbon nitride.

[0126] The appropriate particle space collapse ratio of the negative electrode material and the uniform coating layer on the surface of the negative electrode material can improve the structural stability of the negative electrode material during the lithiation process, reduce the expansion rate of the negative electrode material, and be conducive to the formation of a stable solid electrolyte film on the surface of the negative electrode material. It is also beneficial to the improvement of the conductivity of the negative electrode material, thereby improving the electrochemical performance of the negative electrode material.

[0127] Compared with the prior art, the method for preparing the negative electrode material provided in the embodiment of the present application has the following beneficial effects:

[0128] 1. The pulsed chemical vapor deposition process can precisely control the deposition rate of the second material inside the negative electrode material, and control the deposition rate to increase from the inside to the outside, thereby reserving a portion of pores while depositing the second material inside the negative electrode material precursor, and then precisely adjust the pore volume of the negative electrode material, control the particle space collapse ratio of the negative electrode material, thereby improving the structural stability of the negative electrode material and enhancing the cycle performance and rate performance of the negative electrode material.

[0129] 2. The pulsed chemical vapor deposition process can also form a uniform coating on the surface of the negative electrode material. This uniform coating can further improve the structural stability of the negative electrode material during the lithiation process, reduce the expansion rate of the negative electrode material, and facilitate the formation of a stable solid electrolyte film on the surface of the negative electrode material, thereby improving the cycle performance of the negative electrode material. It also helps to enhance the conductivity of the negative electrode material, thereby improving the electrochemical performance of the negative electrode material.

[0130] 3. This preparation method is simple, efficient, and highly controllable, which is conducive to the large-scale production of negative electrode materials and has excellent commercial prospects.

[0131] See also Figure 2 As shown, an embodiment of the present application further provides a battery. The battery 100 includes a positive electrode sheet 10, a negative electrode sheet 20, a separator 30, and an electrolyte 40. The negative electrode sheet 20 includes a negative electrode active material, which is the negative electrode material described above. The battery 100 prepared using the aforementioned negative electrode material has advantages such as high capacity, high initial efficiency, long cycle life, excellent rate performance, and low expansion.

[0132] The above-mentioned negative electrode material, preparation method thereof, and battery are further described below through specific examples.

[0133] Example 1

[0134] Step 1: Place the silicon monoxide material in an atmosphere furnace, and under the protection of an argon atmosphere, heat it to 950° C. at a heating rate of 3° C. / min, keep it warm for 5 hours, and then cool it to obtain the first product.

[0135] Step 2: Mix the first product and metallic aluminum powder in a mass ratio of 1:0.3, put them into a reactor, introduce protective gas to replace the air, heat to 650°C at a heating rate of 3°C / min, keep warm for 4 hours, and then cool to obtain the second product.

[0136] Step 3: put the second product into the etching solution for purification. The mass ratio of the second product to the etching solution is 1:5, the concentration of the etching solution is 6 mol / L, the etching reaction time is 1.5 h, and the etching reaction temperature is controlled at 25 ° C. After washing and drying, the negative electrode material precursor is obtained.

[0137] Step 4: Place 500 g of the negative electrode material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat it to 750 ° C at a heating rate of 3 ° C / min under the protection of argon atmosphere. Set the acetylene gas flow rate to 2.5 L / min, and pass the carbon source into the pulse generator. Set the pulse frequency to 50 Hz, the pulse duration to 200 ms, and the pulse duration to 3 hours. After turning off the pulser, continue to pass acetylene gas at a flow rate of 2.5 L / min for 2 hours, and cool to obtain the negative electrode material.

[0138] Example 2

[0139] Step 1: Place the silicon monoxide material in an atmosphere furnace, and under the protection of an argon atmosphere, heat it to 970°C at a heating rate of 3°C / min, keep it warm for 6 hours, and then cool it to obtain the first product.

[0140] Step 2: Mix the first product and metallic aluminum powder in a mass ratio of 1:0.3, put them into a reactor, introduce protective gas to replace the air, heat to 650°C at a heating rate of 3°C / min, keep warm for 4 hours, and then cool to obtain the second product.

[0141] Step 3: put the second product into the etching solution for purification. The mass ratio of the second product to the etching solution is 1:10, the concentration of the etching solution is 3 mol / L, the etching reaction time is 2.5 h, and the etching reaction temperature is controlled at 25 ° C. After washing and drying, the negative electrode material precursor is obtained.

[0142] Step 4: Place 500 g of the negative electrode material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat it to 700 ° C at a heating rate of 3 ° C / min under the protection of argon atmosphere. Set the acetylene gas flow rate to 0.5 L / min, and pass the carbon source into the pulse generator. Set the pulse frequency to 500 Hz, the pulse duration to 10 ms, and the pulse duration to 8 hours. After turning off the pulser, continue to pass acetylene gas at a flow rate of 2.5 L / min for 1 hour, and cool to obtain the negative electrode material.

[0143] Example 3

[0144] Step 1: Place the silicon monoxide material in an atmosphere furnace, and under the protection of an argon atmosphere, heat it to 970°C at a heating rate of 3°C / min, keep it warm for 6 hours, and then cool it to obtain the first product.

[0145] Step 2: Mix the first product and metallic aluminum powder in a mass ratio of 1:0.3, put them into a reactor, introduce protective gas to replace the air, heat to 650°C at a heating rate of 3°C / min, keep warm for 4 hours, and then cool to obtain the second product.

[0146] Step 3: put the second product into the etching solution for purification. The mass ratio of the second product to the etching solution is 1:10, the concentration of the etching solution is 3 mol / L, the etching reaction time is 2.5 h, and the etching reaction temperature is controlled at 25 ° C. After washing and drying, the negative electrode material precursor is obtained.

[0147] Step 4: Place 500 g of the negative electrode material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat it to 900 ° C at a heating rate of 3 ° C / min under the protection of argon atmosphere. Set the acetylene gas flow rate to 9.5 L / min, and pass the carbon source into the pulse generator. Set the pulse frequency to 10 Hz, the pulse duration to 800 ms, and the pulse duration to 4 hours. After turning off the pulser, continue to pass acetylene gas at a flow rate of 1.5 L / min for 2 hours, and cool to obtain the negative electrode material.

[0148] Example 4

[0149] Step 1: Place the silicon monoxide material in an atmosphere furnace, and under the protection of an argon atmosphere, heat it to 950° C. at a heating rate of 3° C. / min, keep it warm for 5 hours, and then cool it to obtain the first product.

[0150] Step 2: The first product and metallic magnesium powder are mixed evenly in a mass ratio of 1:0.2, placed in a reactor, a protective gas is introduced to replace the air, heated to 620°C at a heating rate of 3°C / min, kept warm for 5 hours, and then cooled to obtain the second product.

[0151] Step 3: put the second product into the etching solution for purification. The mass ratio of the second product to the etching solution is 1:10, the concentration of the etching solution is 5 mol / L, the etching reaction time is 1.5 h, and the etching reaction temperature is controlled at 25 ° C. After washing and drying, the negative electrode material precursor is obtained.

[0152] Step 4: Place 500 g of the negative electrode material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat it to 950 ° C at a heating rate of 3 ° C / min under the protection of argon atmosphere. Set the acetylene gas flow rate to 10 L / min, and pass the carbon source into the pulse generator. Set the pulse frequency to 10 Hz, the pulse duration to 800 ms, and the pulse duration to 8 hours. After turning off the pulser, continue to pass acetylene gas at a flow rate of 0.1 L / min for 3 hours, and cool to obtain the negative electrode material.

[0153] Example 5

[0154] The specific process of the preparation process refers to Example 1, except that the pulse frequency in step 4 is 20 Hz. The preparation method of other negative electrode materials is basically the same as that in Example 1 and will not be described in detail here.

[0155] Example 6

[0156] The specific process of the preparation process refers to Example 1, except that the pulse frequency in step 4 is 100 Hz. The preparation method of other negative electrode materials is basically the same as that in Example 1 and will not be described in detail here.

[0157] Example 7

[0158] The specific process of the preparation process refers to Example 1, except that the pulse duration in step 4 is 1 hour. The preparation method of other negative electrode materials is basically the same as that in Example 1 and will not be described in detail here.

[0159] Example 8

[0160] The specific process of the preparation process refers to Example 1, except that the pulse duration in step 4 is 6 hours. The preparation method of other negative electrode materials is basically the same as that in Example 1 and will not be described in detail here.

[0161] Comparative Example 1

[0162] The specific process of the preparation process refers to Example 1, except that the carbon deposition in step 4 is a traditional chemical vapor deposition (CVD) technology, specifically, 500g of the negative electrode material precursor is placed in a rotary atmosphere furnace, and the air therein is replaced with an inert gas. Under the protection of an argon atmosphere, the temperature is increased at a rate of 3°C / min to 750°C, and the acetylene gas flow rate is set to 2.5L / min. Acetylene gas is continuously introduced for 5h and cooled to obtain the negative electrode material. The preparation method of the remaining negative electrode materials is basically the same as in Example 1 and will not be described in detail here.

[0163] The negative electrode materials obtained in Examples 1-8 and Comparative Example 1 were subjected to the following tests.

[0164] 1. The negative electrode materials obtained in Examples 1-8 and Comparative Example 1 were tested for performance parameters related to specific surface area, pore volume, particle space collapse ratio P, particle size, tap density, oxygen content, carbon content, scanning electron microscopy, X-ray diffraction, average primary particle size, and average silicon grain size. The results are shown in Table 1. For example, the scanning electron microscopy results of the negative electrode material in Example 1 are as follows: Figure 3 As shown, the X-ray diffraction pattern of the negative electrode material in Example 1 is as follows Figure 4 shown.

[0165] (1) Test methods for specific surface area and specific pore volume of negative electrode materials:

[0166] Using the American Micromeritics ASAP2460 surface area and pore size analyzer, at liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its specific surface area and other properties. Combined with the law of change of adsorption amount with relative pressure during the adsorption process, multiple models can be fitted to calculate the specific surface area and specific pore volume.

[0167] (2) The negative electrode material particle space collapse ratio P is tested by the following method:

[0168] Take 1kg of negative electrode material and measure its pore volume, M. The composite material is then placed in an aluminum-plastic film bag, evacuated to below 10kPa, and sealed. The bag is then placed in an isostatic press at 80MPa. After maintaining this pressure for 1 hour, the pore volume of the composite material is measured as N. The particle space collapse ratio, P, is calculated as (MN) / M.

[0169] (3) Particle size of negative electrode material:

[0170] The median particle size test method refers to GB / T 19077-2016. It can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0171] (4) Test method for tap density:

[0172] Using a vibrator, weigh a certain amount of sample and vibrate 3000 times at 300 times / min to test the tap density.

[0173] (5) Test methods for oxygen content and carbon content:

[0174] The oxygen content was measured by Fourier transform infrared spectrometer, and the overall carbon content was tested by thermogravimetric analysis.

[0175] (6) SEM test:

[0176] SEM characterization was performed on a transmission electron microscope with an operating voltage of 200 kV to observe the structure of the negative electrode material and to scale the thickness of the coating layer.

[0177] (7) Test method for average primary particle size:

[0178] The material is sectioned using a FIB-SEM device, and the sizes of 20 primary particles are measured in the SEM. The average value is the average size of the primary particles.

[0179] (8) Test method for average silicon grain size:

[0180] The XRD pattern of the sample was measured by X-ray diffractometer, the half-maximum width of the sample diffraction peak and the corresponding Bragg angle were obtained by jade software, and the average grain size of nano-silicon was calculated by Scherrer formula D=Kγ / B cosθ.

[0181] Table 1

[0182]

[0183] 2. The electrochemical performance of the negative electrode materials obtained in Examples 1-8 and Comparative Example 1 was tested. The results are shown in Table 2.

[0184] The negative electrode material was mixed with sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive graphite (KS-6) and carbon black (SP) in a ratio of 92:2:2:2:2 to prepare a slurry, uniformly coated on copper foil and dried to form a negative electrode sheet, which was assembled into a button battery in an argon atmosphere glove box. The separator used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate), and the counter electrode used was a metal lithium sheet.

[0185] The above 9 groups of batteries were subjected to discharge specific capacity tests on a Blue Power CT2001A battery testing system. The ratio of the amount of electricity discharged in one hour to the battery capacity is the discharge specific capacity.

[0186] The above 9 groups of batteries were tested for their first coulombic efficiency on a Blue Power CT2001A battery test system with a charge and discharge current of 0.05C, and the first coulombic efficiency was measured.

[0187] The above 9 groups of batteries were cycled for 50 cycles on a Blue Power CT2001A battery test system with a charge and discharge current of 0.25C. After 50 cycles, the battery capacity and capacity retention rate after the cycle were calculated. Among them, the capacity retention rate after 50 cycles at 0.25C = the discharge capacity at the 50th cycle / the discharge capacity at the first cycle * 100%. For example, the cycle performance curve of the battery prepared using the negative electrode material in Example 1 is as follows: Figure 5 shown.

[0188] Table 2

[0189]

[0190] The above results show that:

[0191] Figure 3 This is a scanning electron microscope image of the negative electrode material in Example 1. Figure 3 It can be seen from the scanning electron microscope image that the surface of the negative electrode material is relatively smooth and the particles of the negative electrode material are not broken. Figure 4 is the XRD pattern of the negative electrode material in Example 1, Figure 4 The XRD pattern shows that the three strong peaks at 28.4°, 47.3° and 56.1° correspond to the three strong peaks of silicon (JCPDS No. 27-1402), and there is basically no impurity phase. According to the Scherrer formula, the silicon grain size can be calculated to be 3.5nm. After testing, the pore volume of the negative electrode material obtained in Example 1 is 0.09cm 3 / g, the particle space collapse ratio P is 0.25, the average size of the silicon grains in the negative electrode material is 3.5nm, the median particle size of the negative electrode material is 5μm, and the specific surface area is 5m 2 / g, the powder compaction density is 1.2g / cm 3 , an oxygen content of 5%, a carbon content of 33% by mass, and an average primary particle size of 10 nm for the silicon material in the negative electrode material. The results show that the negative electrode material obtained in Example 1 has an appropriate pore volume and particle space collapse ratio P, as well as excellent performance parameters such as an appropriate specific surface area and a high compaction density.

[0192] Figure 5 The cycle performance curve of the button battery prepared using the negative electrode material in Example 1 is as follows: Figure 5As can be seen from the graph, the button-type battery prepared using the negative electrode material of Example 1 exhibits excellent cycling performance. After 50 cycles at a current of 0.25C, the capacity retention rate still reaches 83.3%. This indicates that the negative electrode material of this example has an appropriate pore volume and particle space collapse ratio P, which not only improves the structural stability of the negative electrode material but also improves its cycling performance, thereby enhancing the electrochemical performance of the battery.

[0193] The negative electrode materials obtained in Examples 2-8 also have suitable pore volume and particle space collapse ratio P, as well as excellent properties such as suitable specific surface area and high compaction density. The batteries made using the negative electrode materials obtained in Examples 2-8 also have high specific capacity and first efficiency, significantly improved volume retention rate and low expansion rate.

[0194] In Comparative Example 1, the conventional chemical vapor deposition technology was used. However, the carbon deposition rate of the carbon source in the material could not be precisely controlled to adjust the pore volume of the composite negative electrode material and control the particle space collapse ratio of the composite negative electrode material. As a result, the pore volume of the negative electrode material in Comparative Example 1 (0.21 cm 3 / g) is too large, which can easily cause deformation of the outer surface of the negative electrode material, thereby leading to capacity decay and reduced cycle stability of the prepared battery; and the particle space collapse ratio (0.95) is too high, the rigidity of the negative electrode material is weak, and there are many internal pores. Although it can effectively alleviate the volume expansion of silicon, the large volume shrinkage of the negative electrode material will cause the electrolyte to be absorbed into the material, causing side reactions and severe capacity decay.

[0195] It can be seen that compared with Comparative Example 1, the negative electrode materials obtained in Examples 1-8 all have suitable pore volume and particle space collapse ratio P, and the various structural data and electrochemical test results are excellent, indicating that the negative electrode materials in the examples of the present application have good structural stability, can effectively reduce the expansion rate, and exhibit excellent electrochemical performance.

[0196] It will be understood that the above embodiments are merely exemplary embodiments for illustrating the principles of the present invention, and the present invention is not limited thereto. Those skilled in the art will appreciate that various modifications and improvements can be made without departing from the spirit and substance of the present invention, and such modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A negative electrode material, characterized in that: The invention comprises an active material and a coating layer, wherein the coating layer is disposed on at least a portion of the surface of the active material, the active material comprises a first matrix and a second matrix, the negative electrode material has pores, the pore volume of the negative electrode material is M, the pore volume of the negative electrode material measured after being maintained at a pressure of 80 MPa for 1 hour is N, and the particle space collapse ratio of the negative electrode material is P, where P=(MN) / M, wherein 0.002 cm 3 / g≤M≤0.12cm 3 / g, 0.05≤P≤0.

85.

2. The negative electrode material according to claim 1, characterized in that The first matrix includes at least one element or combination selected from silicon, germanium, antimony, tin and boron.

3. The negative electrode material according to claim 1, characterized in that The first substrate comprises a silicon-based material, and the silicon-based material satisfies at least one of the following conditions: (1) The silicon-based material includes amorphous silicon, crystalline silicon, or a composite of crystalline silicon and amorphous silicon; (2) The silicon-based material includes at least one of silicon oxide and silicon alloy.

4. The negative electrode material according to claim 1, characterized in that: The second matrix satisfies at least one of the following conditions: (1) the second matrix comprises a carbon material, wherein the carbon material comprises at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers and graphene; (2) The second matrix includes a non-carbon material, and the non-carbon material includes at least one of a metal, a metal oxide, a silicide, a silicate, a phosphate, a titanate, and an aluminum borate.

5. The negative electrode material according to claim 1, characterized in that At least some of the particles of the second matrix are located inside the particles of the first matrix, and / or at least some of the particles of the first matrix are located inside the particles of the second matrix.

6. The negative electrode material according to claim 1, characterized in that The coating layer satisfies at least one of the following conditions: (1) The coating layer includes a carbon material, and the carbon material includes at least one of graphene, soft carbon and hard carbon; (2) The coating layer includes a metal oxide layer, and the material of the metal oxide layer includes at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide and vanadium oxide; (3) The coating layer includes a nitride layer, and the material of the nitride layer includes at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride; (4) The thickness of the coating layer is 0.1 nm to 100 nm.

7. The negative electrode material according to claim 3, characterized in that The silicon-based material satisfies at least one of the following conditions: (1) The average particle size of the primary particles of the silicon-based material is 1 nm to 100 nm; (2) The average grain size of the silicon-based material is 0.5 nm to 15 nm.

8. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following conditions: (1) The median particle size of the negative electrode material is 0.2 μm to 15 μm; (2) The specific surface area of ​​the negative electrode material is 0.8 m 2 / g~15m 2 / g; (3) The average diameter of the pores is 0.5 nm to 20 nm; (4) The powder compaction density of the negative electrode material is 0.8 g / cm 3 ~1.5g / cm 3 .

9. The negative electrode material according to claim 1, characterized in that Calculated by mass percentage, the negative electrode material satisfies at least one of the following conditions: (1) The second matrix comprises a carbon material, and the carbon content of the negative electrode material is 5% to 70% based on the mass of the negative electrode material; (2) Based on the mass of the negative electrode material, the content of oxygen in the negative electrode material is less than or equal to 10%.

10. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 9.

Citation Information

Cited By

  • Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN121355253A

  • Negative electrode material and battery

    EP4822776A1